2015
DOI: 10.1155/2015/690961
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Corneal Collagen Crosslinking Redo in Private Practice: Risk Factors and Safety

Abstract: Objective. To report the rate of progression of keratectasia after primary crosslinking (CXL) and evaluate the safety and efficiency of CXL redo. Materials and Methods. We conducted a retrospective analysis of the patients who underwent CXL between 2010 and 2013 at the Beirut Eye Specialist Hospital, Lebanon. Progression of keratectasia was based on the presence of an increase in maximum keratometry of 1.00 D, a change in the map difference between two consecutive topographies of 1.00 D, a deterioration of vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 38 publications
2
35
2
Order By: Relevance
“…The failure rates ranged from 0%12 to 16.5% 36. While the recorded postoperative period for documentation of KC progression following SCXL varied from early postoperative months34 to several postoperative years32,35 and even reached 10 years in Raiskup et al37 Our study recorded 4.1% failure rate at 5 years which is similar to some studies38 and lower than others 34,36…”
Section: Discussionsupporting
confidence: 86%
“…The failure rates ranged from 0%12 to 16.5% 36. While the recorded postoperative period for documentation of KC progression following SCXL varied from early postoperative months34 to several postoperative years32,35 and even reached 10 years in Raiskup et al37 Our study recorded 4.1% failure rate at 5 years which is similar to some studies38 and lower than others 34,36…”
Section: Discussionsupporting
confidence: 86%
“…11 Good levels of efficacy and safety have been reported for CXL retreatments in eyes with previous CXL, but showing signs of keratoconus progression associated to allergic conjunctivitis and eye rubbing. 12 The aim of the current study was to evaluate the clinical results of epi-off CXL during a 7-year follow-up, evaluating not only visual, refractive, corneal curvature and pachymetric changes, but also potential corneal elevation and anterior segment alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown an increase in keratometry readings related to allergic conjunctivitis necessitating a second CXL (Antoun et al. ). However, we show that such progression can be reversed with anti‐inflammatory treatment using adequate topical and systemic treatment including antihistamines, corticosteroids or cyclosporin.…”
Section: Discussionmentioning
confidence: 94%